Scots pine (Pinus sylvestris L.) radial growth dynamics in forest stands in the vicinity of “Akmenes cementas” plant - Stravinskienė, Vida; Erlickytė-Marčiukaitienė, Regina (Journal of Environmental Engineering and Landscape Management, 2009)
Investigation of Scots pine annual radial increment was carried out in the surroundings of one of the largest pollution sources in Lithuania – the cement plant “Akmenes cementas”. The main objective of the investigation was to analyse possible impact of climatic and anthropogenic factors on the radial growth of Scots pine (Pinus sylvestris L.) stands growing in the local impact zone of the plant. Investigation has shown that in peat‐bog sites active vegetation period temperature higher than the long‐term average influences the formation of radial increment positively (r = 0.22–0.34; p < 0.05), and July precipitation higher than the long‐term average causes the reduction of radial increment (r = ‐0.25; p < 0.05) of the investigated pines. Analysis of the relation between pine radial increment and plant emissions has shown that the strongest correlations are in the closest vicinity of the plant (r = ‐0.63; p < 0.05). Weaker, but statistically significant relations were found between radial increment of pines growing at a distance of 5–10 km from the plant and plant emissions (r = ‐0.49; p < 0.05), and for the most distant pine correlations became insignificant (p > 0.05). Linear regression results have shown that changes of the radial increment of pine stands closest to the plant are the biggest and they decrease with distance from the plant. Paprastosios pušies (Pinus sylvestris L.) Radialiojo prieaugio dinamika „Akmenės cemento“ gamyklos aplinkos medynuose Santrauka. Paprastosios pušies (Pinus sylvestris L.) metinio radialiojo prieaugio pokyčių tyrimai buvo atliekami cemento gamyklos „Akmenės cementas“ aplinkoje. Pagrindinis šio tyrimo tikslas – nustatyti galimą klimato ir antropogeninių veiksnių įtaką paprastosios pušies (Pinus sylvestris L.) medynų radialiajam prieaugiui gamyklos aplinkoje. Nustatyta, kad gamyklos aplinkoje augančiuose raistašilio (Carico–sphagnosa) miško tipo pušynuose teigiamos įtakos pušų radialiojo prieaugio formavimuisi turi aukštesnė nei vidutinė daugiametė aktyviosios vegetacijos oro temperatūra (r = 0,22–0,34; p < 0,05), o didesnis nei vidutinis daugiametis liepos mėnesio kritulių kiekis lemia radialiojo prieaugio mažėjimą (r = –0,25; p < 0,05). Nagrinėjant pušų radialiojo prieaugio sąsają su gamyklos teršalų kiekiu, stipriausias koreliacinis priklausomumas nustatytas artimiausioje gamyklos aplinkoje (iki 5 km) (r = –0,63; p < 0,05). Silpnesnis, tačiau statistiškai patikimas priklausomumas nustatytas tarp vidutiniu atstumu nuo gamyklos (5–10 km) augančių pušų prieaugio ir gamyklos teršalų kiekio. Toliausiai nuo gamyklos (per 10–20 km) augančių pušų radialiojo prieaugio sąsaja su bendruoju ir pavienių teršalų kiekiu yra statistiškai nepatikima (p > 0,05). Iš tiesinės regresinės analizės rezultatų akivaizdu, kad pušynų artimiausioje gamyklos aplinkoje metinio radialiojo prieaugio pokyčiai yra didžiausi, o tolstant nuo gamyklos mažėja. Reikšminiai žodžiai: paprastoji pušis, radialusis prieaugis, oro temperatūra, kritulių kiekis, aplinkos tarša. Динамика радиального прироста сосны обыкновенной (Pinus sylvestris L.) в древостоях, растущих в окрестностях завода „Акмянес цементас“ Резюме. Исследования годового радиального прироста сосны обыкновенной (Pinus sylvestris L.) были проведены в окрестностях цементного завода „Акмянес цементас“. Главная цель исследования – определить возможное влияние климатических и антропогенных факторов на изменение радиального прироста сосны обыкновенной (Pinus sylvestris L.), произрастающей в окрестностях цементного завода. Исследования показали, что на формирование радиального прироста сосен, растущих в сосновых древостоях леса типа Carico-sphagnosa, позитивное влияние оказывает температура воздуха, превышающая среднюю многолетнюю температуру воздуха активной вегетации (r = 0.22–0.34; p < 0.05), а количество осадков в июле, превышающее среднее многолетнее количество, способствует уменьшению радиального прироста (r = –0.25; p < 0.05). Корреляционный анализ зависимости радиального прироста сосен от эмиссии завода показал сильнейшую связь (r = –0.63; p < 0.05) на расстоянии до 5 км от завода. На расстоянии 5–10 км от завода корреляционная связь уменьшается, а при дальнейшем удалении от завода статистически не доказана. Результаты линейной регрессии показали, что наибольшие изменения радиального прироста сосен происходят на расстоянии до 5 км от завода, а с увеличением расстояния от завода они уменьшаются. Ключевые слова: сосна обыкновенная, радиальный прирост, температура воздуха, количество осадков, загрязнение окружающей среды. First Published Online: 14 Oct 2010